Immobilized 1,2-Bis(guanidinoalkyl)benzenes: Potentially Useful for the Purification of Arsenic-Polluted Water - Suzuki, Noriyuki; Kishimoto, Kaito; Yamazaki, Kohei; Kumamoto, Takuya; Ishikawa, Tsutomu; Margetić, Davor (Synlett, 2013)
Guanidines can act as ligands for various organic and inorganic ions. We have previously synthesized polymer-supported aromatic bisguanidine derivatives and evaluated their potential for removing arsenic from polluted water. In this work, we designed and synthesized the corresponding aliphatic bisguanidine derivatives, and we demonstrated that they show greater affinity for arsenic acid than do the previous aromatic ligands. The newly synthesized HypoGel resin-anchored aliphatic bisguanidines might serve as useful recyclable scavengers for the removal of arsenic from polluted water.
Keywords: chelates; complexes; ligands; green chemistry; polymers